2009
DOI: 10.1007/s00464-009-0473-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the curability of early gastric cancer with endoscopic submucosal dissection

Abstract: When risk factors including positive ulcer findings and larger size and upper location of tumors are combined, ESD should be performed more carefully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
32
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 14 publications
8
32
0
1
Order By: Relevance
“…Similarly, Oda et al [16] reported that tumor location in the upper or middle third of the stomach, tumor size [21 mm, and ulceration were each associated with piecemeal resection of ECG, affecting curability by ESD. In addition, Ohnita et al [17] showed by multivariate analysis that ulceration is a primary cause of incomplete resection of EGC by ESD. Moreover, ulceration significantly increases the time required for the operation and is a risk factor for perforation [16,26,27], although it is not a cause of postoperative bleeding [16,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Oda et al [16] reported that tumor location in the upper or middle third of the stomach, tumor size [21 mm, and ulceration were each associated with piecemeal resection of ECG, affecting curability by ESD. In addition, Ohnita et al [17] showed by multivariate analysis that ulceration is a primary cause of incomplete resection of EGC by ESD. Moreover, ulceration significantly increases the time required for the operation and is a risk factor for perforation [16,26,27], although it is not a cause of postoperative bleeding [16,28].…”
Section: Discussionmentioning
confidence: 99%
“…Submucosal dissection of F2 lesions is difficult because maintaining an appropriate dissection depth requires skill. Overly shallow dissection performed to avoid perforation may cause heat denaturation of the excised specimen, making detailed histopathological examination of the sample difficult and thus hindering clinical judgment [16,17,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the accuracy of T staging in EGC with ulcer is very low [14]. Third, the presence of ulceration interferes with complete resection and promotes a long procedure time and high risk of adverse events such as bleeding and perforation [3,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…However, improvement and exacerbation of ulceration repeat in patients with ulcerative EGC as a malignant cycle [5]. Moreover, EGC combined with ulcer is associated with a low curative resection rate and high risk of adverse events such as perforation and bleeding [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%